Factors affecting the implementation of Corporate Entrepreneurship in a South African Bank - Okoko, Marie-Lou Dibwe (My University, 2014)
The South African economy has undergone significant change over the past two decades, moving from an isolated state that bred inefficiencies through limited economies of scale and a lack of competition to a much more open environment that has helped reduce price pressures and improve productivity. Apart from significant trade liberalisation, the South African government has followed conservative fiscal policies, introduced inflation targeting, undertaken limited privatisation, eliminated capital controls for foreign investors and reduced exchange controls on residents. The South African economy – in line with many other economies – has become increasingly services orientated (Nedbank Business Review, 2011). Furthermore, the South African banking and financial services sector plays a critical role in the realisation of the developmental aspirations of any country; it is a catalyst for economic growth as it creates platforms for citizens to transact for goods and services. Following the aftermath of the most significant financial crisis the world has ever experienced in 2008, one of the insights gained by the South African financial services industry from the crisis is that it needs to take a holistic or system-wide view of the financial sector by considering both the soundness of the institutions within the system and the system as a whole in the process of providing products and services to its customer base. On the other hand, the competition within this industry is high and organisations need to continuously find new ways to adapt to the rapid changes in the business landscape. Corporate Entrepreneurship has therefore never been more important for any organisation operating in this sector. An exploratory or qualitative research methodology was employed based on semi-structured interviews with a non-probability sample of 16 respondents. All respondents were existing employees of Bank X operating at senior to middle iii management level. The respondents were from both the corporate and retail segment of Bank X and both male and female from all race groups. The research showed that although Corporate Entrepreneurship exists in Bank X, its translation from being a strategic aspiration of management into clear measurable goals within the organisation is not clear. In its efforts to engage its workforce, Bank X needs to ensure that its vision and strategic goals are clearly communicated throughout the organisation and each division needs to have clearly defined and measurable goals that link back to the vision and mission set out by executive management of Bank X. Both the literature and research are in agreement that Corporate Entrepreneurship is the way forward for any company operating in the 21st century that aims to remain competitive.
MBA thesis
Keywords: Entrepreneurship; Corporate entrepreneurship